(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Aspilia africana is an herbal plant widespread in Africa used for medicinal purposes and also used by pregnant women for health related issues. This study was aimed at investigating the teratogenic effect of aqueous leaf extract of Aspilia africana on the dentate gyrus of albino wistar rat fetuses. Twenty (20) female adult rats weighing between 190-205g were used for this study. The rats were divided into four groups; control, low dose, medium dose and high dose with each group containing five rats. Pregnancy was induced by caging the female rats with sexually matured males. The presence of vaginal plug and tail structure in the vaginal smear the following morning confirmed coition, and it was regarded as day 0 of pregnancy. The control group was given distilled water. The low dose, medium dose, and the high dose groups received 750mg/kg, 1000mg/kg, and 1250mg/kg body weight of aqueous leaf extract of Aspilia africana through an orogastric tube from day 7-11 of gestation. On the 20th day of gestation, the animals were sacrificed using chloroform-inhalation method. Their fetuses were harvested via uterectomy, the brain was excised and fixed in 10% buffered formalin, and then routine histological processes were carried out. Staining was done using Haematoxylin and Eosin method. Histological observation of the dentate gyri of experimental groups revealed marked distortion, reduction of the polymorphic layer, hyperplasia and hypertrophy of cells in the molecular and granular layer especially in the high dose group whose mothers received 1250mg/kg of the extracts. The result suggests high doses of aqueous leaf extract of Aspilia africana may be teratogenic to the dentate gyrus of Wistar rat fetuses.